Development of pineapple mango juice blend - Estrella, Mavelle M. (1998)
A study on the development of Canned Pineapple-Mango Juice Blend was undertaken. A reference juice blend was used as basis for determining the desired Brix/acid ratio for the proposed juice blend. In Phase I of the study, the most acceptable formulation for the juice blend was determined. From the nine different formulations with varying ratios of pineapple and mango, blends with the proporitons 50:50, 70:30 and 80:20 mango to pineapple juice were not significantly different from each other. For economic reasons, 50:50 ratio was used in the study. The water dilution to the preferred juice was also determined with the 1:1 juice to water ratio being more preferred than the other ratios. Phase II involved determination of the best method of heat treatment. Hot filling versus heat processing for 15 minutes at 100C were compared and results show that thermal processing for 15 minutes at 100C was the best and safest method of treatment based on process calculations and microbiological examination. Consumer acceptability test revealed that the thermally processed juice blend was of good quality and it was liked moderately by most panelists. Phase III of the study involved characterization of the preferred processed juice blend. It was observed that the soluble solid content was much higher for the processed juice than the freshly prepared juice blend. The pH and % titratable acidity however were not very much affected by processing of the juice. These values lead to a higher sugar-acid ratio for the processed juice.